50 years of India, China : crossing a bridge of dreams - Deshpande, G. P. (Govind P.), 1938-; Acharya, Alka. (New Delhi : Tulika, 2001)
Papers presented at a seminar organized by the Institute of Chinese Studies, New Delhi and India International Centre; most on socio-economic topics.
Includes bibliographical references (p. 518-524) and index.
Keywords: India -- Economic conditions -- 1947- -- Congresses; China -- Economic conditions -- 1949- -- Congresses; India -- Social conditions -- 1947- -- Congresses; China -- Social conditions -- 1949- -- Congresses; India -- Relations -- China -- Congresses..; China -- Relations -- India -- Congresses